Predictive factors for treatment success of transforaminal epidural steroid injection in lumbar disc herniation-induced sciatica - GÜNDÜZ, OSMAN HAKAN (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2020)
Background/aim: The aim of this study was to identify predictive factors for treatment success in transforaminal epidural steroid injection in patients with lumbar disc herniation-induced sciatica. Materials and methods: A total of 219 patients who were diagnosed with unilateral sciatica and underwent transforaminal epidural steroid injections at the level of L4-5, L5-S1, or S1 neural foramina between March 2016 and May 2018 were retrospectively analyzed. The presence of transitional vertebrae and the grade of nerve root compression were evaluated by a radiologist. Data including age, sex, body mass index, duration of symptoms, injection levels, and pain scores were recorded. Pain scores were evaluated using the numerical rating scale. Treatment success was defined as a >= 50% decrease in pain scores at 3 months. Results: The study included 118 female and 101 male patients with a mean age of 43.65 +/- 12.18 years. The mean duration of symptoms was 25.64 +/- 2.17 weeks. Although the duration of symptoms was longer in patients for whom treatment failed, it did not reach statistical significance. Decreased pain scores at 1 h had a significant effect on treatment success (p = 0.012, odds ratio (OR): 1.015, 95% confidence interval (CI), 1.003-1.026). Conclusions: Our study results suggest that a decreased pain score at 1 h is a predictor for a favorable three-month response to transforaminal epidural steroid injection in patients with lumbar disc herniation-induced sciatica.
Keywords: Epidural injection; herniated disc; low back pain; back pain with radiation; magnetic resonance imaging sciatica; LOW-BACK-PAIN; RADICULAR PAIN; MRI-FINDINGS; DOUBLE-BLIND; OUTCOMES